How Culture Shapes Customers: A Cross-Continent Analysis of Apps Reviews Using NLP Techniques - Azolin Kotsifas, Maria Fernanda; Lüders, Ricardo; Silva, Thiago H. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de Dados, 2025)
Understanding customers’ feedback is essential for businesses to improve products and adapt to different markets. This study analyzes 100,000 app reviews from Uber, Instagram, and WhatsApp across six countries (Brazil, U.S., Australia, India, U.K., and South Africa) to assess whether user concerns are global or culturally influenced. Using BERTopic for topic modeling, zero-shot classification for topic assignment, and Aspect-Based Sentiment Analysis, we identify twelve key topics in reviews. While some topics are shared globally, others are country-specific. For example, Uber’s reliability was a major concern in South Africa and Australia, while Brazilian users discussed WhatsApp voice messages more frequently. These findings help businesses detect market-specific trends, benchmark competitors, and address regional needs strategically.